2019
DOI: 10.3390/buildings9060142
|View full text |Cite
|
Sign up to set email alerts
|

Monitored Indoor Environmental Quality of a Mass Timber Office Building: A Case Study

Abstract: A broad range of building performance monitoring, sampling, and evaluation was conducted periodically after construction and spanning more than a year, for an occupied office building constructed using mass timber elements such as cross-laminated timber (CLT) floor and roof panels, as well as glue-laminated timber (GLT) beams and columns. This case study contributes research on monitoring indoor environmental quality in buildings, describing one of the few studies of an occupied mass timber building, and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…Cowsheds buildings can present microbial load by means of direct dust settlement due to a complex combination of local environmental conditions, large crowding of animals and airflow when serving food, milking, hygienic procedures or the expulsion and return of cattle to and from pastures (Gnat et al, 2018; Łagowski et al, 2020). All parameters related to the indoor microclimate are consistent with those recorded for human environments (Marcu et al, 2021; Shelton et al, 2002; Stenson et al, 2019; Tseng et al, 2021), although it seems that the aerosol load with potentially pathogenic micro‐organisms for livestock is much higher. Moreover, these conidia or dermatophyte hyphae tend to proliferate from air to other organic compounds, such as food, milk, litter and dust, among others (Tseng et al, 2021; van Rhijn & Bromley, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…Cowsheds buildings can present microbial load by means of direct dust settlement due to a complex combination of local environmental conditions, large crowding of animals and airflow when serving food, milking, hygienic procedures or the expulsion and return of cattle to and from pastures (Gnat et al, 2018; Łagowski et al, 2020). All parameters related to the indoor microclimate are consistent with those recorded for human environments (Marcu et al, 2021; Shelton et al, 2002; Stenson et al, 2019; Tseng et al, 2021), although it seems that the aerosol load with potentially pathogenic micro‐organisms for livestock is much higher. Moreover, these conidia or dermatophyte hyphae tend to proliferate from air to other organic compounds, such as food, milk, litter and dust, among others (Tseng et al, 2021; van Rhijn & Bromley, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…Additional problems are caused by the construction material (especially wood), which forms a culture medium for the growth of microorganisms and fungi. Solid wood buildings can present microbial load by means of direct dust settlement due to a complex combination of local environmental conditions [ 3 , 4 ]. Arguably, old heritage buildings must be monitored in order to minimize the risks to the health of visitors and employees, to optimize the maintenance costs, and prior to their inclusion in sightseeing tours.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, bacteria that can survive frequent, harsh cleanings may be better able to withstand variations in environmental conditions within patient rooms (Velazquez et al, 2019). While the unique design and occupancy of individual buildings make it difficult to compare indoor microbial communities between structures, it is important to note that many observational studies of microbial communities within the built environment, such as office spaces and homes, identify thousands of unique taxa (Kembel et al, 2012;Stenson et al, 2019). The present study identified approximately 1000 taxa, despite the high occupancy and activity level typical of a hospital, lending credence to the idea that patient rooms with regular cleaning are a harsh environment for bacteria, and that this cleaning regime is a stronger selection force than sunlight exposure.…”
Section: Discussionmentioning
confidence: 99%